Tm-Ho codoped fiber saturable absorber based passive Q-switching with subsidiary pump. (22nd June 2015) - Tao, Mengmeng; Feng, Guobin; Wang, Fei; Yu, Ting; Shen, Yanlong; Wang, Zhenbao; Ye, Xisheng
Abstract: A Tm-Ho codoped fiber saturable absorber based passively Q-switched fiber laser with a subsidiary pump is built. The repetition rate improvement with a subsidiary pump is observed. The average increases of the repetition rate are about 1 kHz and 1.5 kHz with a 15 mW and 20 mW subsidiary pump, respectively. A maximum repetition rate of 28.2 kHz is obtained with a 20 mW subsidiary pump. Simulations are carried out, validating the repetition rate improvement capacity of the subsidiary pump method.